ENGARUH KUALITAS PELAYANAN DAN PENETAPAN HARGA TERHADAP KEPUASAN DAN MINAT BELI ULANG PADA JASA LAUNDRY SEPATU TOUCH AND CLEAN PEKANBARU - , T. Firli Musfar, Reza Rahmadi , Hj. Henni Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
Most consumers who buy shoes only focus on wearing it. In fact, apart from being bought and worn, shoes also require maintenance. To clean various types of shoes, you must use certain liquids that have a low acidity level so that the material is not easily damaged or destroyed. Besides that, you also have to use a special brush that is dense, stiff and soft. This has caused the emergence of many shoe laundry service businesses in Pekanbaru City, one of which is Touch and Clean Pekanbaru. This study aims to see the effect of service quality and pricing on satisfaction and repurchase intention at Touch And Clean Pekanbaru shoe laundry service. The population in this study is the population in this study are people in the city of Pekanbaru who have used Touch & Clean shoe laundry services. Meanwhile, to determine the number of samples in this study using the Slovin formula, and obtained a sample of 100 people. Data analysis used path analysis with SPSS version 26. The results of the study found that service quality and pricing had a significant effect on customer satisfaction. Then service quality, pricing and customer satisfaction have a significant effect on repurchase intention. Furthermore, service quality and pricing have a significant effect on repurchase intention through customer satisfaction. Keywords: Service Quality, Pricing, Consumer Satisfaction, Repurchase Intenti